1970
DOI: 10.1242/jeb.53.3.529
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the Respiratory Pumps to Hypoxia in the Rainbow Trout (Salmo Gairdnert)

Abstract: 1. Unanaesthetized rainbow trout, when subjected to a lowered Po2 of the inspired water, show an increase in amplitude of pressures recorded from the buccal and opercular cavities. Pressure amplitudes were commonly found to be 0.5 cm of water in resting trout and increased 4- or 5-fold as inspired Po2 was reduced. Differential pressures across the gills also increased with hypoxia. 2. Typically the minute volume in a 400-600 g trout increased from about 0.2 to 0.6 l/kg/min when the inspired Po2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Consistent with other studies (e.g. Hughes and Saunders, 1970 ; Giacomin et al, 2019 ), we observed that fish significantly increased their GVR and the amplitude of opercular movements with increasing water temperature to increase oxygen supply to metabolizing tissues to delay the onset of anaerobic metabolism. Moreover, acute exposure of fish to warm water meant that fish engaged ASR earlier at higher oxygen saturation levels.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies (e.g. Hughes and Saunders, 1970 ; Giacomin et al, 2019 ), we observed that fish significantly increased their GVR and the amplitude of opercular movements with increasing water temperature to increase oxygen supply to metabolizing tissues to delay the onset of anaerobic metabolism. Moreover, acute exposure of fish to warm water meant that fish engaged ASR earlier at higher oxygen saturation levels.…”
Section: Discussionsupporting
confidence: 92%
“…In the past it has been common for assay of pollutants to be carried out using lethal or near lethal doses and while such methods have their value, it is equally important to know more of the sublethal effects of pollutants and how to assay them. The techniques developed in studies of fish respiratory physiology clearly have some value in this respect and the methods described here are relatively simple ones to which could be added ECG recording and the measurement of ventilation volume and oxygen consumption by similar methods (Hughes and Saunders, 1970). The particular parameter chosen here is of especial interest with respect to suspended solid pollutants but it may also be important in other cases.…”
Section: Assay Of Pollutantsmentioning
confidence: 99%
“…As a result, the unidirectionally ventilated gills of water-breathing animals typically extract 70 to 85% of the O 2 from the inhaled water (e.g. [11][12][13][14]).…”
Section: Introductionmentioning
confidence: 99%